1997
DOI: 10.1128/iai.65.9.3594-3599.1997
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 (IL-12) and IL-18 synergistically induce the fungicidal activity of murine peritoneal exudate cells against Cryptococcus neoformans through production of gamma interferon by natural killer cells

Abstract: We examined the ability of interleukin-12 (IL-12) and IL-18 to induce the production of gamma interferon (IFN-␥) and nitric oxide (NO) by murine peritoneal exudate cells (PEC) and to stimulate the growth-inhibitory activity of these cells against Cryptococcus neoformans. PEC produced IFN-␥ and NO when stimulated with a combination of IL-12 and IL-18 but little or no IFN-␥ or NO when either cytokine was used alone. PEC anticryptococcal activity was mediated by IFN-␥ and NO production, since it was completely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(92 citation statements)
references
References 34 publications
6
85
0
1
Order By: Relevance
“…23 This cytokine appears to be critical for mounting a T helper 1 (Th1) response 24 as it promotes the secretion of IFN-c by natural killer (NK) cells 25 which in turn activates Mw for microbial killing. 26 This activation includes stimulation of inducible NO synthase and formation of reactive oxygen species (both of which are central to the microbicidal response) and is necessary for proin¯ammatory cytokine production. 27 Accordingly, we examined the capacity to generate oxygen free radicals and reactive nitrogen species by Mw upon stimulation in TRAP-de®cient and wildtype congenic-strain mice, as well as their capacity to secrete proin¯ammatory cytokines, including IL-12.…”
Section: Discussionsupporting
confidence: 91%
“…23 This cytokine appears to be critical for mounting a T helper 1 (Th1) response 24 as it promotes the secretion of IFN-c by natural killer (NK) cells 25 which in turn activates Mw for microbial killing. 26 This activation includes stimulation of inducible NO synthase and formation of reactive oxygen species (both of which are central to the microbicidal response) and is necessary for proin¯ammatory cytokine production. 27 Accordingly, we examined the capacity to generate oxygen free radicals and reactive nitrogen species by Mw upon stimulation in TRAP-de®cient and wildtype congenic-strain mice, as well as their capacity to secrete proin¯ammatory cytokines, including IL-12.…”
Section: Discussionsupporting
confidence: 91%
“…IL-18, formerly designated interferon (IFN)-γ inducing factor, is a recently cloned cytokine with a molecular weight of 18 kDa, synthesized in Kupffer cells and activated macrophages. 10,11) The activities associated with IL-18 are induction of IFN-γ production in Th1 cells and natural killer (NK) cells, especially in the presence of IL- 12,12) and enhancement of the cytotoxic activity of these cells through the Fas ligand-mediated mechanism. 13,14) The effect of IL-18 on human CD8 + T cell responses has not been established.…”
mentioning
confidence: 99%
“…Many other studies have shown the positive effect of IL-18 DNA as a gene adjuvant to DNA vaccination [52,53]. The predominant function of IL-18 in the immune system is the stimulation of the Th1-type immune response through production of IFN-␥ [20,21]. IL-18 also enhances the proliferation of T cells in a dose-dependent manner, an effect that is not IFN-␥ dependent [20].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a DNA vaccine consisting of plasmid vectors encoding gag/pol and env genes of FeLV-A/Glasgow-1 [19] protected cats against both the establishment of persistent viraemia and latency when administered together with plasmids encoding feline IL-12 and IL-18 [1]. The rationale for using both cytokines was that IL-12 and IL-18 act synergistically on T and natural killer (NK) cells to stimulate the production of interferon-gamma (IFN-␥), a mediator of the induction of CTL [20,21]. In the previous vaccination study [1], those animals that were protected by the vaccine had higher virus-specific effector CTL in the peripheral blood and lymphoid organs than cats that became persistently viraemic [4].…”
Section: Introductionmentioning
confidence: 99%